2011
DOI: 10.1016/j.jctb.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Circumference of 3-connected claw-free graphs and large Eulerian subgraphs of 3-edge-connected graphs

Abstract: The circumference of a graph is the length of its longest cycles. Results of Jackson, and Jackson and Wormald, imply that the circumference of a 3-connected cubic n-vertex graph is Ω(n 0.694 ), and the circumference of a 3-connected claw-free graph is Ω(n 0.121 ).We generalize and improve the first result by showing that every 3-edge-connected graph with m edges has an Eulerian subgraph with Ω(m 0.753 ) edges. We use this result together with the Ryjáček closure operation to improve the lower bound on the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The shortness exponent of cubic polyhedral graphs is not known. The currently known best lower bound, due to Bilinski et al [2], is λ ≥ x ≈ 0.7532, where x is the real root of 4 1/x − 3 1/x = 2. The currently known best upper bound is λ ≤ log 23 22 ≈ 0.9858 due to Grünbaum and Walther [10].…”
Section: Preliminariesmentioning
confidence: 99%
“…The shortness exponent of cubic polyhedral graphs is not known. The currently known best lower bound, due to Bilinski et al [2], is λ ≥ x ≈ 0.7532, where x is the real root of 4 1/x − 3 1/x = 2. The currently known best upper bound is λ ≤ log 23 22 ≈ 0.9858 due to Grünbaum and Walther [10].…”
Section: Preliminariesmentioning
confidence: 99%
“…Indeed,the proof of Theorem 3.4 also shows that if Conjecture 1.4 is not true, then for any integer k with k ≥ 5, there exist infinitely many essentially 4-edge-connected graphs H with minimum edge degree at least k such that for any closed trail T in H , dom H (T ) = O(|E(H )| α ). Recall that h = |V ≥4 (H)| and H is a counterexample of Conjecture 1.4 .It should be mentioned here that Bilinski et al[3] recently showed that every essentially 3-edge-connected graph H has a closed trail T with dom H (T ) ≥ ( |E(H )|12) β + 2, where β ≈ 0.753; consider the preimage version of Theorem 1.2 in[3].So, if Conjecture 1.4 is not true, then the gap of bounds on max T ((log dom H (T ))/|E(H )|) between the essentially 4-edge-connected case and the essentially 3-edge-connected case would be only the difference between α and β.…”
mentioning
confidence: 99%
“…3 , v 4 be four consecutive vertices of C v and let p = pen H (v). We subdivide the edges v 1 v 2 and v 3 v 4 exactly p times and obtain the paths v…”
mentioning
confidence: 99%
“…This conjecture remained open until a counterexample was found in 1946 by Tutte [11]. There has since been extensive research concerning longest cycles in graphs, see [6] for more references. We use |G| to denote the order of a graph G, i.e., the number of vertices in G; and refer to the length of a longest cycle in G as the circumference of G. We will be concerned with lower bounds on the circumference of 3-connected cubic graphs.Barnette [4] showed that every 3-connected cubic graph of order n has circumference Ω(log n).…”
mentioning
confidence: 99%
“…This conjecture was confirmed by Jackson [8], with c = log 2 (1+ √ 5)−1 ≈ 0.694. Bondy and Simonovits [7] constructed an infinite family of 3-connected cubic graphs with circumference Θ(n log 9 8 ) ≈ Θ(n 0.946 ).Recently, Bilinski, Jackson, Ma and Yu [6] showed that every 3-connected cubic graph of order n has circumference Ω(n α ), where α ≈ 0.753 is the real root of 4 1/x − 3 1/x = 2. This is proved by reducing the problem to one about Eulerian subgraphs in 3-edge-connected graphs.In this paper, we further improve this lower bound by considering certain vertex weighted, 2-connected cubic graphs (multiple edges allowed).…”
mentioning
confidence: 99%